2018
DOI: 10.16952/pns.2018.15.2.49
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality beyond Access: A Multilevel Analysis of Neonatal, Infant, and Under-Five Child Mortality Using the Indian Demographic and Health Survey 2015~2016

Abstract: Purpose:The purpose of this study was to derive contextual indicators of medical provider quality and assess their relative importance along with the individual utilization of antenatal care (ANC) and institutional births with a skilled birth attendant (SBA) in India using a multilevel framework. Methods: The 2015~2016 Demographic and Health Survey (DHS) from India was used to assess the outcomes of neonatal, infant, and under-five child mortality. The final analytic sample included 182,980 children across 28,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
4
1
0
Order By: Relevance
“…Tigray region had lower risk of under-five mortality compared to other regions except Addis Ababa city administration. This finding is in agreement with other studies which found that region is determinant factor of infant and under-five mortality in Ethiopia [ 5 , 7 , 9 , 27 , 32 ], Kenya [ 36 ], Nigeria [ 15 , 16 , 37 ], Mozambique [ 38 ], Ghana [ 23 , 39 ], India [ 40 ], and Bangladesh [ 24 ]. This might be because of difference in basic infrastructure distribution like health coverage and regional variations in economic development among regions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Tigray region had lower risk of under-five mortality compared to other regions except Addis Ababa city administration. This finding is in agreement with other studies which found that region is determinant factor of infant and under-five mortality in Ethiopia [ 5 , 7 , 9 , 27 , 32 ], Kenya [ 36 ], Nigeria [ 15 , 16 , 37 ], Mozambique [ 38 ], Ghana [ 23 , 39 ], India [ 40 ], and Bangladesh [ 24 ]. This might be because of difference in basic infrastructure distribution like health coverage and regional variations in economic development among regions.…”
Section: Discussionsupporting
confidence: 93%
“…The richest women had significant reduction in under-five mortality compared to the poorest women. This result agrees with various findings [ 14 , 16 , 24 , 26 , 35 , 40 , 42 , 43 ], but it disagrees with the finding of study conducted in Nigeria [ 29 ]. In Ethiopia, many previous related studies also showed that the variable wealth index was not significantly determined under-five mortality [ 31 , 41 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 78%
“…And, Addis Ababa city had a lower U5M and higher in other four regions compared with the Tigray region. This finding is in agreement with other studies which found that there were regional variation for infant and under-five mortality in Ethiopia [5,7,9,27], Kenya [36], Nigeria [15,16,37], Mozambique [38], Ghana [23,39], India [40], and Bangladesh [24] showed that regional variation significantly affects U5M. These differences might be because of difference in basic infrastructure distribution like health coverage and regional variations in economic development.…”
Section: Plos Onesupporting
confidence: 92%
“…The richest women had significant reduction in under-five mortality with compared to the poorest women. This result agrees with various findings [14,16,24,26,35,40,[42][43][44]. Whereas, it is not agreed with a study conducted in Nigeria [29].…”
Section: Plos Onesupporting
confidence: 77%
“…Most previous studies 9 , 10 , 11 on geographic variation of health system performance have focused on health outcomes of care, with process quality being only rarely examined in terms of geographic distribution. A few existing studies 12 , 13 on between-areas variation in process quality have relied on single-level analysis, such as national or state levels, which may conceal inequalities at lower levels.…”
Section: Introductionmentioning
confidence: 99%